Blood flow simulation of stented aneurysm model - Abdul Kadir, Mohammed Rafiq; Taib, I.; Osman , K.; Abdul Hamid, M. H. (Springer Berlin Heidelberg, 2008)
Two methods are available for treatment of aneurysm — open surgery or endovascular aneurysm repair. The first treatment uses synthetic polymeric graft to replace the diseased site, whilst the second involves strengthening the blood vessel wall with an expandable metallic stent. Endovascular aneurysm repair is gaining popularity over open surgery, but the technique is relatively new without long-term follow-up outcome. Pre-clinical evaluations are therefore crucial to minimise possible complications such as endoleaks, stent migration, stent failure and other complications. In this study, the effectiveness of stent geometry in terms of protecting the weak wall of an aneurysm sack from the impact of blood flow was studied. Three dimensional model of a simplified aneurysm model was constructed with a thickness of 2mm throughout. Two already expanded stent geometries were modelled and positioned inside the aneurysm site. Blood flow was simulated across the aneurysm sack using a commercially available fluid dynamics software. The results showed a slight increase in pressure within the aneurysm region under simulated blood flow. When metallic stents were introduced, the pressure at the aneurysm site was reduced. This study confirms the effectiveness of the endovascular aneurysm repair in terms of protecting the blood vessel from a possible rupture.